Color Stability of Polished and Glazed Dental Porcelain in Chlorhexidine - Mehran Norbakhsh; Ezatollah Jalalian; Mohammad Hasan Salari; Sogol Saberi; Sara Tahmasbi Moradi (Islamic Dental Association of Iran, 2017)
Background and Aim: Discoloration is a major concern with regard to the use of tooth-colored restorations. Type of restorative material and surface treatment are believed to play a role in this regard. This study sought to compare the color change of glazed and polished dental porcelain after 30 days of immersion in chlorhexidine (CHX). Materials and Methods: In this in vitro, experimental study, 20 discs with 10 mm diameter and 2 mm thickness were fabricated of A1 shade of Noritake porcelain using a gypsum mold. All samples had one opaque layer. They were then randomly divided into two groups of 10. Glaze powder was added to porcelain in group 1, and group 2 was polished using a polishing kit. The CIE L*a*b color parameters of samples were then measured using a spectrophotometer. All samples were immersed in 0.02% chlorhexidine solution for 30 days and color parameters were then measured again. Change in each color parameter was compared between the two groups (polished and glazed) using t-test. Results: After 30 days of immersion in CHX, ∆E was 0.76±0.16 in the glazed and 0.89±0.16 in the polished group. The difference in this regard between the two groups was not significant (P=0.092). Conclusion: Both polishing and glazing confer optimal color stability to dental porcelain.